FRI0043 Heritability assessment of cartilage collagen metabolism. a twin study on circulating pro-collagen iia n-terminal pro-peptide (piianp). (23rd January 2014) - Munk, H. L.; Svendsen, A. J.; Kyvik, K. O.; Sørensen, G. L.; Hjelmborg, J. V.; Junker, P.
Abstract : Background: Collagen is produced and secreted as a precursor molecule with C-and N-terminal extensions termed procollagen peptides. In the extracellular space these are cleaved off by specific C- and N-peptidases after which collagen can participate in fibril formation. Since procollagen propeptides are released from the parent molecule in a stoichiometric manner, the concentration of these peptides provides an opportunity to assess the current biosynthetic activity of the parent collagen species. Recently, the heritability of cartilage oligomeric matrix protein (COMP) in serum was estimated to 40%. (1 ) Objectives: The aim of the investigation was to estimate heritability on circulating collagen IIA N-propeptide (PIIANP) by studying mono- and dizygotic twin pairs. Methods: A total of 602 healthy monozygotic (MZ) and dizygotic (DZ) twin individuals aged 18-55 years were recruited from the Danish Twin Registry. PIIANP was measured by competitive ELISA. The similarity of circulating PIIANP among MZ and DZ twins was assessed by means of intraclass correlations for the traits. The extent to which variation in a trait is attributable to genetics (heritability) can be estimated quantitatively through variance components analysis. The phenotypic (P) variance in a trait can be separated into four variance components: variance due to additive genetic effects (A), genetic dominance (D), shared (family) environment (C) and non-shared (individual) environment (E), e.i., P = A + D + C + E. In agreement with standard practice, we assume no epistasis (genetic inter-locus interaction) and no gene-environment interaction or correlation. Results: The intraclass correlation for PIIANP in MZ twins and DZ twins was 0.69 vs. 0.46. In the variance component analysis, ACE was the best fitting model. Additive genetic effects explained 45%, shared environment 24% and non-shared environment 31% of the total variance. Conclusions: Our findings suggest that genetic factors have a considerable impact on the serum level of PIIANP. However, shared and common environmental factors are important modifiers as well. The close similarity between the heritability figures of PIIANP and COMP indicate that the expression of these two integral constituents of hyaline cartilage is coordinated or that they are processed in the extracellular space by shared metabolic pathways. References: Williams FM, Andrew T, Saxne T, Heinegard D, Spector TD, MacGregor AJ. The heritable determinants of cartilage oligomeric matrix protein. Arthritis and rheumatism. 2006 Jul;54(7):2147-51. Disclosure of Interest: None Declared